Insular Pharmacopoeias: Ethnobotanical Characteristics of Medicinal Plants Used on the Adriatic Islands - Łuczaj, Łukasz; Jug-Dujaković, Marija; Dolina, Katija; Jeričević, Mirjana; Vitasović-Kosić, Ivana (Frontiers in Pharmacology, 2021)
The Adriatic islands in Croatia, usually divided into two archipelagos – the Kvarner and Dalmatian Islands – is one of the largest groups of islands in Europe. Over 40 islands are still inhabited. Unfortunately the traditional use of medicinal plants was never properly documented there. Our data comes from 343 interviews carried out in 36 islands, including the 15 largest islands of the archipelago. The medicinal plants are mainly used to make herbal infusions or decoctions, occasionally medicinal liqueurs, syrups, compresses, or juices squeezed out of raw plants. We recorded the use of 146 taxa, among them 124 with at least one medicinal purpose and 15 only for tea. The frequency curve of use is relatively steep – several plants are used very frequently and most are reported only by one or two informants, which can be explained both by the large geographical spread of the area, and even more so by the devolution of local knowledge and disappearance of gathering practices due to specialization in tourism, modernization and depopulation. Most of the gathered plants already occur in ancient and medieval herbals and are a part of the pan-Mediterranean pharmacopoeia.